Kingship and propinquity - Houghton, Nigel; British Broadcasting Corporation. Television Service (Milton Keynes : Open University, 1973)
Discusses about kingship
Converted into VHS 1/2 in.
Title from title screen
Executive producer, Michael Philps
Speaker : Michael Anderson, Simon Albury
Keywords: Kings and rulers; Rites and ceremonies